Sleep Quantity and Quality of Ontario Wildland Firefighters Across a Low-Hazard Fire Season. Issue 12 (December 2017) - McGillis, Zachary; Dorman, Sandra C.; Robertson, Ayden; Larivière, Michel; Leduc, Caleb; Eger, Tammy; Oddson, Bruce E.; Larivière, Céline
Abstract : Objective: The aim of the study was to assess the sleep quality, quantity, and fatigue levels of Canadian wildland firefighters while on deployment. Methods: Objective and subjective sleep and fatigue measures were collected using actigraphy and questionnaires during non-fire (Base) and fire (Initial Attack and Project) deployments. Results: Suboptimal sleep quality and quantity were more frequently observed during high-intensity, Initial Attack fire deployments. Suboptimal sleep was also exhibited during non-fire (Base) work periods, which increases the risk of prefire deployment sleep debt. Self-reported, morning fatigue scores were low-to-moderate and highest for Initial Attack fire deployments. Conclusions: The study highlights the incidence of suboptimal sleep patterns in wildland firefighters during non-fire and fire suppression work periods. These results have implications for the health and safety practices of firefighters given the link between sleep and fatigue, in a characteristically hazardous occupation.